Personalized Medicine in Cerebrovascular Neurosurgery: Precision Neurosurgical Management of Cerebral Aneurysms and Subarachnoid Hemorrhage - Achrol, Achal Singh; Steinberg, Gary K. (Frontiers in Surgery, 2016)
Cerebral aneurysms are common vascular lesions. Little is known about the pathogenesis of these lesions and the process by which they destabilize and progress to rupture. Treatment decisions are motivated by a desire to prevent rupture and the devastating morbidity and mortality associated with resulting subarachnoid hemorrhage (SAH). For patients presenting with SAH, urgent intervention is required to stabilize the lesion and prevent re-rupture. Those patients fortunate enough to survive a presenting SAH and subsequent securing of their aneurysm, must still face a spectrum of secondary sequelae, which can include cerebral vasospasm, delayed ischemia, seizures, cerebral edema, hydrocephalus, and endocrinologic and catecholamine-induced systemic dysfunction in cardiac, pulmonary, and renal systems. Increased focus on understanding the pathophysiology and molecular characteristics of these secondary processes will enable the development of targeted therapeutics and novel diagnostics for improved patient selection in personalized medicine trials for SAH. In unruptured cerebral aneurysms, treatment decisions are less clear and currently based solely on treating larger lesions, using rigid aneurysm size cutoffs generalized from recent studies that are the subject of ongoing controversy. Further compounding this controversy is the fact that the vast majority of aneurysms that come to clinical attention at the time of a hemorrhagic presentation are of smaller size, suggesting small aneurysms are indeed not benign lesions. As such, patient-specific biomarkers that better predict which aneurysms represent high-risk lesions that warrant clinical intervention are of vital importance. Recent advancements in genomic and proteomic technologies have enabled the identification of molecular characteristics that may prove useful in tracking aneurysm growth and progression, and identifying targets for prophylactic therapeutic interventions. Novel quantitative neuroimaging technologies have also recently emerged, capable of noninvasive characterization of hemodynamic factors, inflammation, and structural changes in aneurysmal walls. The combined use of these quantitative neuroimaging and molecular-based approaches, called Radiogenomics, is a technique that holds great promise in better characterizing individual aneurysms. In the near future, these Radiogenomic techniques may help improve quality of life and patient outcomes via patient-specific approaches to the treatment of unruptured cerebral aneurysms, and personalized medical management of secondary processes following aneurysmal SAH.